A floating 10kV power cable and its manufacturing method

By combining gradient foamed insulation layers and nanomaterials, a 10kV power cable with self-floating and high insulation performance is achieved, solving the problem that traditional cables require external buoyancy devices. It is suitable for power supply to floating photovoltaic, wind power and aquaculture at sea.

CN122716094BActive Publication Date: 2026-11-06ZHONGTIAN TECH SUBMARINE CABLE CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611224958.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-11-06
Estimated Expiration
2046-08-13

AI Technical Summary

Technical Problem

Existing 10kV medium-voltage power cables cannot float on their own and require external buoyancy devices, resulting in structural redundancy, heavy weight, and high cost. Furthermore, the existing wet insulation design poses safety hazards.

Method used

It adopts a structure consisting of a three-core stranded conductor, a gradient foamed insulation layer, a steel wire armor layer, and a weather-resistant sheath layer from the inside out. The gradient foamed insulation layer integrates insulation and buoyancy functions, and the density gradient is controlled by combining nanomaterials and a three-section feeding process, eliminating the need for an external buoyancy device.

Benefits of technology

It enables the cable to float, reduces the overall density, and improves the insulation breakdown field strength and mechanical properties. It is suitable for power supply of floating photovoltaic, wind power and aquaculture at sea, and has excellent fatigue resistance and simplified structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122716094B_ABST
    Figure CN122716094B_ABST
Patent Text Reader

Abstract

This invention discloses a floating 10kV power cable and its manufacturing method. The cable, from the inside out, comprises a three-core stranded conductor, a closed-cell foamed buoyancy buffer layer, a steel wire armor layer, and a weather-resistant sheath layer. Each stranded conductor, from the inside out, comprises a conductor, a conductor shielding layer, a gradient foamed insulation layer, an insulation shielding layer, a longitudinal water-blocking layer, and a metal shielding layer. The density of the gradient foamed insulation layer is radially gradient-distributed, with the inner layer having a higher density than the outer layer. The gradient foamed insulation layer comprises a matrix resin, additives, a foaming system, and a cross-linking system. The advantages of this invention are that it can float without an external buoyancy device, has an insulation breakdown field strength ≥30kV / mm, and a space charge density ≤2C / m². 3 It is suitable for supplying power to floating photovoltaic, wind power and aquaculture systems at sea.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power cable technology, and in particular to a floating 10kV power cable and its manufacturing method. Background Technology

[0002] With the rapid development of offshore floating photovoltaic power generation, floating wind power generation, and aquaculture, the demand for medium-voltage power cables capable of long-term floating operation on water is becoming increasingly urgent. Traditional 10kV medium-voltage power cables typically have a density of 1.2~1.5 g / cm³. 3 It is much denser than water (1.0 g / cm³). 3 Since they cannot float directly on the water surface, they must rely on external buoyancy devices (such as floats, airbags, etc.) to achieve floating installation.

[0003] In the prior art, for example, Chinese patent application CN120280207A discloses a floating power cable based on communication engineering, which provides buoyancy by setting a snap-fit ​​part and an airbag on the outside of the cable. However, this external buoyancy structure has the following drawbacks:

[0004] (1) The airbag or float is an independent component, and its reliability in combination with the cable body is poor. It is prone to damage and detachment in complex environments such as wind, waves, ultraviolet radiation and marine organisms. (2) The external buoyancy structure increases the outer diameter of the cable, which leads to a significant increase in the bending stiffness of the cable and a large minimum bending radius, which is not conducive to laying and winding. (3) There is an interface gap between the external airbag and the cable body, which is prone to stress concentration points during long-term operation, accelerating cable fatigue aging. (4) The airbag structure does not have insulation function, and the cable still needs a complete insulation layer, resulting in redundant overall structure, large weight and high cost.

[0005] Furthermore, existing floating submarine cables (such as dynamic submarine cables used in offshore wind farms) mostly adopt a wet insulation structure design, which allows seawater to enter the armor layer and relies on the internal water-blocking structure to protect the insulated core. However, this design has extremely high requirements for water-blocking performance, and once the water-blocking layer fails, seawater will directly contact the insulation layer, posing a serious safety hazard.

[0006] Meanwhile, the existing submarine cable insulation layer uses solid cross-linked polyethylene (XLPE), with a density of approximately 0.92~0.95 g / cm³. 3 Although lighter, the overall density of the cable is still significantly greater than that of water when combined with copper conductors, metal shielding layers, and armor layers. Summary of the Invention

[0007] The purpose of this invention is to provide a floating 10kV power cable and its manufacturing method, which can float without an external buoyancy device, has an insulation breakdown field strength ≥30kV / mm, and a space charge density ≤2C / m. 3 It is suitable for supplying power to floating photovoltaic, wind power and aquaculture systems at sea.

[0008] The above-mentioned technical objective of the present invention is achieved through the following technical solution: A floating 10kV power cable comprises, from the inside out, a three-core stranded conductor, a closed-cell foamed buoyancy buffer layer, a steel wire armor layer, and a weather-resistant sheath layer. Each stranded conductor comprises, from the inside out, a conductor, a conductor shielding layer, a gradient foamed insulation layer, an insulation shielding layer, a longitudinal water-blocking layer, and a metal shielding layer. The density of the gradient foamed insulation layer is distributed radially in a gradient manner, with the inner layer having a higher density than the outer layer. The gradient foamed insulation layer comprises a matrix resin, additives, a foaming system, and a crosslinking system. The matrix resin is a blend of low-density polyethylene and ethylene-vinyl acetate copolymer. The additives include one-dimensional potassium titanate whiskers, two-dimensional boron nitride nanosheets, and nano-alumina with surface-grafted voltage stabilizers. The overall density of the cable is 0.87~0.92 g / cm³. 3 .

[0009] Preferably, the thickness of the gradient foamed insulation layer is 4.5~5.5mm, and the gradient foamed insulation layer includes an inner layer, a middle layer and an outer layer; The inner layer accounts for 30% of the overall thickness and has a density of 0.88~0.92 g / cm³. 3 With a pore size of 3~10μm and a closed-cell rate of ≥92%, this region mainly serves as an insulation function under high electric field strength. The intermediate layer accounts for 40% of the total thickness and has a density of 0.78~0.85 g / cm³. 3 With a pore size of 10~25μm and a closed-pore ratio of ≥87%, this region takes into account both insulation and buoyancy transition. The outer layer accounts for 30% of the overall thickness and has a density of 0.62~0.72 g / cm³. 3 With a pore size of 25~45μm and a closed-pore ratio of ≥82%, this region mainly provides buoyancy support.

[0010] Preferably, in the matrix resin, the one-dimensional potassium titanate whiskers are K2O·6TiO2, with an addition amount of 0.5~1.0 phr, a diameter of 0.3~0.8 μm, and a length of 10~30 μm, and their main function is to provide mechanical reinforcement and support for the cell wall skeleton.

[0011] The amount of the two-dimensional boron nitride nanosheets added is 1.0~2.0 phr, the thickness is 5~15 nm, and the sheet diameter is 200~500 nm. The two-dimensional boron nitride nanosheets are arranged in parallel in the cell wall to form a gas barrier layer, which prevents gas from inside the cell from permeating outward and causing the cell to collapse. The main functions are heat conduction and heat dissipation, electric field homogenization, and gas permeation barrier.

[0012] The amount of nano-alumina added to the surface-grafted voltage stabilizer is 2.0~3.0 phr, and the amount added decreases from the inner layer to the outer layer. The particle size is 20~40 nm. The polar groups at the end of the grafted chain on the surface serve as nucleation sites for bubbles, reducing the nucleation energy barrier and promoting an increase in the number and size of bubbles. Its main functions are deep trapping of charges, voltage stabilization, and bubble nucleation.

[0013] Preferably, the specific preparation method of the nano-alumina with surface-grafted voltage stabilizer is as follows: first, the nano-alumina is pretreated with silane coupling agent KH-570 to obtain modified nano-alumina with double bonds on the surface; then, the voltage stabilizer N-(4-anilinephenyl)-maleimide is grafted onto the surface of the nano-alumina by free radical polymerization, with a grafting rate of 12~18wt%, forming a "flexible organic shell" on the surface of the nano-alumina. This shell has the following functions: The aniline group in the voltage stabilizer molecule can capture high-energy electrons and suppress the initiation of electrical treeing; Organic shells exhibit better compatibility with LDPE / EVA matrices than inorganic nanoparticles, reducing interfacial defects. The polar groups at the ends of the grafted chain can serve as nucleation sites for the foaming gas, promoting the uniform refinement of the foam pores. The flexible shell absorbs energy when the bubble wall is subjected to force, preventing the bubble wall from rupturing.

[0014] Preferably, the foaming system comprises: 2.5-4.5 phr of azodicarbonamide coated with stearic acid as the main foaming agent, 1.0-2.0 phr of sodium bicarbonate as the auxiliary foaming agent, and 0.3-0.5 phr of zinc oxide and 0.3-0.5 phr of zinc stearate as foaming activators.

[0015] Preferably, the crosslinking system comprises: 1.5~2.5 phr of dicumyl peroxide, 0.5~1.0 phr of triallyl isocyanurate as a co-crosslinking agent, and 0.5 phr of antioxidant 1010.

[0016] Preferably, the three-core stranded conductor is a copper conductor stranded with a cross-section of 50~400mm², and the conductor shielding layer is a semi-conductive cross-linked polyethylene with a thickness of 0.6~1.0mm, a volume resistivity of ≤500·Ω·cm, and a cross-linking degree of ≥80%. This layer adopts the same cross-linking system as the insulating shielding layer to ensure that the interfacial bonding strength is ≥1.5N / mm.

[0017] Preferably, the insulating shielding layer is a semi-conductive cross-linked polyethylene with a thickness of 0.6~1.0 mm.

[0018] The longitudinal water-blocking layer is constructed by overlapping and wrapping two layers of water-blocking tape with an overlap rate of ≥30%. The water-blocking tape is an expansion-type water-blocking tape with a thickness of 0.5mm, an expansion rate of ≥10mm / min, an expansion height of ≥12mm, and contains more than 60wt% superabsorbent polymer (SAP).

[0019] The metal shielding layer is made of longitudinally wrapped copper strip or tinned copper wire. The copper strip is ≥0.1mm thick and its width matches the outer diameter of the cable. The tinned copper wire has a braiding density ≥80% and a single wire diameter of 0.15~0.20mm. It is used to carry fault current and provide electromagnetic shielding.

[0020] The closed-cell foamed buoyancy buffer layer is made of closed-cell foamed polypropylene, with a minimum thickness of 3.0~5.0 mm and a density of 0.55~0.65 g / cm³. 3 With a foam pore size of 50~100μm and a closed-cell rate of ≥75%, this layer not only provides additional buoyancy, but also serves to buffer external mechanical impacts and protect the internal insulation structure.

[0021] The steel wire armor layer uses galvanized steel wire with a double-layer gap armor, with a diameter of 1.5~3.0mm. The gaps in the armor are filled with water-blocking rope. The steel wire armor layer is coated with an asphalt anti-corrosion layer with a thickness of 0.5~1.0mm, which can effectively offset torsional loads and adapt to the swaying motion of the floating platform in wind and waves.

[0022] Preferably, the weather-resistant sheath layer is a blend of weather-resistant thermoplastic polyurethane, chlorinated polyethylene and ethylene-vinyl acetate copolymer in a mass ratio of 6:3:1, with added UV-resistant additive UV-531 at 2.0 phr, mildew inhibitor isothiazolinone at 1.0 phr and antioxidant 1010 at 2.0 phr. This sheath layer has excellent resistance to salt spray, ultraviolet radiation, microorganisms and wear.

[0023] A method for manufacturing a floating 10kV power cable includes the following steps: S1 employs a three-segment feeding, three-layer co-extrusion and gradient chemical foaming cross-linking synchronous molding process to sequentially form a conductor shielding layer, a gradient foaming insulation layer and an insulation shielding layer on the outside of the conductor. S2, a longitudinal water-blocking layer is wrapped around the outside of the insulating shielding layer; S3, covered with a metal shielding layer; S4, three-core stranded cable, gap extruded closed-cell foamed buoyancy buffer layer; S5, galvanized steel wire forms a steel wire armor layer through a double-layer gap-type armor; S6, extruded weather-resistant sheath layer.

[0024] Preferably, step S2 specifically comprises: An extrusion unit consisting of three tandem single-screw extruders and a three-layer co-extrusion crosshead is used to continuously complete the molding of the conductor shielding layer, the gradient foamed insulation layer and the insulation shielding layer, respectively. The barrel of the intermediate single-screw extruder is divided into three temperature-controlled sections. Different uniformly mixed gradient foamed insulation layer materials with different formulations are fed into each section through an independent loss-in-weight feeder. The gradient foamed insulation layer materials extruded from the die head form radial layers and directly enter the horizontal vulcanizing tube for foaming and cross-linking. The horizontal vulcanizing tube is filled with high-purity nitrogen and is divided into three sections. The first section accounts for 20% of the length and has a temperature of 185~190℃, the second section accounts for 50% of the length and has a temperature of 205~220℃, and the third section accounts for 30% of the length and has a temperature of 165~170℃. After cooling and shaping in a cooling water tank, the gradient foamed insulation layer is formed.

[0025] In summary, the present invention has the following beneficial effects: 1. By using a gradient foamed insulation layer, the insulation and buoyancy functions of a 10kV power cable are integrated into the same structural layer, breaking the traditional design paradigm of "the insulation layer is only responsible for insulation, and buoyancy depends on external devices," thus simplifying the cable structure.

[0026] 2. The high-density inner layer of the gradient foamed insulation layer ensures the insulation reliability of the high electric field area, the low-density outer layer provides buoyancy, and the middle layer achieves a smooth transition. This "functional zoning" design allows the overall density to be reduced without sacrificing the electrical performance of critical areas.

[0027] 3. By leveraging the synergistic effect of nano-alumina and voltage stabilizers, the technical challenge of reduced dielectric strength in foamed insulation materials is solved, resulting in a higher breakdown field strength in the foamed insulation layer compared to traditional solid XLPE. This is the key material innovation of this invention.

[0028] 4. The innovative process route of three-section feeding, layered melting inside a single extruder, and synchronous foaming and cross-linking outside the die head achieves precise control of radial density gradient on a single production line. The process is highly feasible and suitable for industrial production.

[0029] 5. The double-layer reverse armor structure combined with the flexibility of the gradient foam insulation layer gives the cable excellent fatigue resistance when subjected to dynamic loads such as the swaying of floating platforms and the impact of wind and waves. After 100,000 dynamic bending cycles, the electrical performance still meets the standard requirements.

[0030] 6. The overall density of the cable is 0.87~0.92 g / cm³. 3It can float stably in freshwater and seawater without any external buoyancy device. It is easy to lay, simple to maintain, and highly reliable. It is especially suitable for offshore floating photovoltaic, floating wind power, aquaculture, temporary water power supply and other scenarios. Attached Figure Description

[0031] Figure 1 This is an overall cross-sectional view of the floating 10kV power cable of the present invention; Figure 2 This is a cross-sectional diagram of the three-core stranded conductor in the invented floating 10kV power cable; In the diagram: 1-Three-core stranded conductor, 11-Conductor, 12-Conductor shielding layer, 13-Gradient foamed insulation layer, 131-Inner layer, 132-Middle layer, 133-Outer layer, 14-Insulating shielding layer, 15-Longitudinal water-blocking layer, 16-Metallic shielding layer, 2-Closed-cell foamed buoyancy buffer layer, 3-Steel wire armor layer, 4-Weather-resistant sheath layer. Detailed Implementation

[0032] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings. These embodiments do not constitute a limitation on the present invention.

[0033] Example: Rated voltage 8.7 / 10kV, three-core stranded conductor 1; Structure as Figure 1 and 2 As shown: Conductor 11: Stranded copper conductor, 1+6 structure, single wire diameter 2.76mm, conductor 11 diameter 7.5mm, gap filled with water-blocking adhesive; Conductor shielding layer 12: Semi-conductive XLPE, thickness 0.6mm, outer diameter 8.7mm; Gradient foamed insulation layer 13: total thickness 4.5mm, inner layer 131 is 1.35mm (density 0.89g / cm³). 3 The middle layer 132 is 1.80mm thick (density 0.81g / cm³). 3 The outer layer 133 is 1.35mm thick (density 0.69g / cm³). 3 ), outer diameter 17.7mm; Insulating shielding layer 14: Semi-conductive XLPE, thickness 0.6mm, outer diameter 18.9mm; Longitudinal water-blocking layer 15: Double-layer expansion water-blocking tape wrapped around, 1.0mm thick, 20.9mm outer diameter; Metal shielding layer 16: Copper strip longitudinally wrapped, thickness 0.1mm, outer diameter 21.1mm; Closed-cell foamed buoyancy buffer layer 2: Three-core stranded cable, gap closed-cell foamed buoyancy buffer layer 2, made of closed-cell foamed PP, with a minimum thickness of 4.0mm and an outer diameter of 54mm; Steel wire armor layer 3: 2 layers of galvanized steel wire, 2.0mm in diameter and 60mm in outer diameter; Weather-resistant sheath layer 4: TPU / CPE / EVA blend, 3.5mm thick, finished outer diameter 67mm.

[0034] Preparation method: S1, prepare three types of feed respectively: Conductor shielding material: Semi-conductive XLPE masterbatch (containing 25~30wt% carbon black and LDPE matrix), directly fed into extruder A; Insulating shielding material: Same as conductor shielding material, fed into extruder C; Gradient foamed insulation layer 13: Using zoned feeding technology, insulation materials with different foaming formulations are fed into the three temperature control zones of extruder B through three loss-in-weight feeders to achieve radial density gradient.

[0035] The specific formula and zoned feeding scheme for the gradient foamed insulation layer 13 are as follows: Inner layer 131 (corresponding to the inner layer 131 of gradient foamed insulation layer 13 with a thickness of 30%): LDPE (MFR=2.0g / 10min): 85phr; EVA (VA content 10%): 15phr; one-dimensional potassium titanate whiskers: 0.8phr; two-dimensional boron nitride nanosheets: 1.5phr; nano-alumina with surface-grafted voltage stabilizer: 3.0phr; stearic acid-coated azodicarbonamide: 2.0phr; sodium bicarbonate: 0.8phr; zinc oxide: 0.4phr; zinc stearate: 0.4phr; dicumyl oxide: 2.0phr; triallyl isocyanurate: 0.8phr; antioxidant 1010: 0.5phr.

[0036] Middle layer 132 (corresponding to 40% thickness of the middle layer 132 in the gradient foamed insulation layer 13): LDPE (MFR=2.0g / 10min): 85phr; EVA (VA content 10%): 15phr; one-dimensional potassium titanate whiskers: 0.8phr; two-dimensional boron nitride nanosheets: 1.5phr; nano-alumina with surface-grafted voltage stabilizer: 2.5phr; stearic acid-coated azodicarbonamide: 3.0phr; sodium bicarbonate: 1.2phr; zinc oxide: 0.4phr; zinc stearate: 0.4phr; dicumyl oxide: 2.0phr; triallyl isocyanurate: 0.8phr; antioxidant 1010: 0.5phr.

[0037] Outer layer 133 (corresponding to the outer layer 133 of the gradient foamed insulation layer 13, which has a thickness of 30%): LDPE (MFR=2.0g / 10min): 85 phr; EVA (VA content 10%): 15 phr; One-dimensional potassium titanate whiskers: 0.8 phr; Two-dimensional boron nitride nanosheets: 1.5 phr; Nano-alumina with surface-grafted voltage stabilizer: 2.0 phr; Stearic acid-coated azodicarbonamide: 4.0 phr; Sodium bicarbonate: 1.5 phr; Zinc oxide: 0.4 phr; Zinc stearate: 0.4 phr; Dicumyl oxide: 2.0 phr; Triallyl isocyanurate: 0.8 phr; Antioxidant 1010: 0.5 phr.

[0038] The three layers of materials were premixed in three high-speed mixers (800-1000 rpm, 5-8 min, ≤60℃) and then fed into three loss-in-weight feeders.

[0039] Simultaneous molding of extrusion and foam crosslinking An extrusion unit consisting of three tandem single-screw extruders (extruders A, B, and C) and a three-layer co-extrusion crosshead is used. Extruder B is a special extruder for foam insulation, with a screw length-to-diameter ratio L / D = 28:1 and a compression ratio of 2.5:1. The screw structure is a separation barrier screw, equipped with a mixing section and a shearing section to ensure uniform dispersion of the foaming agent and avoid premature decomposition.

[0040] The barrel of extruder B is equipped with three temperature control zones, and the temperature and feeding scheme of each zone are as follows:

[0041] The melts from the three extruders (A, B, and C) converge in a three-layer co-extrusion crosshead, with the die head temperature controlled at 165-175°C. The conductor shielding layer 12 (extruder A) is in direct contact with the three-core stranded conductor 1, the gradient foamed insulation layer 13 (extruder B) is in the center, and the insulation shielding layer 14 (extruder C) is the outermost layer. The melt pressure inside the die head is controlled at 15-25 MPa to ensure the foaming agent remains soluble during extrusion, and the pressure drops sharply after leaving the die head, triggering foaming.

[0042] The extruded cable cores directly enter the horizontal vulcanizing tube (dry crosslinking, DCP vulcanization system), which is divided into three sections: Preheating section: temperature 180~190℃, length accounts for 20% of the total length of the vulcanizing tube. The purpose is to allow DCP to decompose initially to generate free radicals, triggering the cross-linking reaction, and at the same time to allow the foaming agent to begin to decompose and generate gas. Foaming and cross-linking stage: temperature 200~220℃, length accounts for 50%. In this stage, the cross-linking reaction and the foaming reaction are carried out simultaneously. The formation of the cross-linking network limits the excessive expansion of the bubbles and ensures the closed-cell structure. The shaping section is 160-170℃, accounts for 30% of the length, and has a cross-linking degree of over 80%. The cell structure is fixed to prevent the bubbles from collapsing or merging.

[0043] The nitrogen pressure inside the vulcanizing tube is controlled at 0.8~1.2MPa to suppress excessive bubble expansion and prevent melt rupture. The running speed (traction speed) of the wire core inside the vulcanizing tube is 8~15m / min, adjusted according to the cable specifications.

[0044] After exiting the vulcanizing tube, the wire core passes through a water-cooling tank (segmented cooling: first segment 60℃ → second segment 40℃ → third segment 20℃), with the cooling rate controlled at 5~10℃ / min to prevent the cell structure from cracking or the insulation layer from cracking due to excessive temperature difference.

[0045] The key to this "gradient chemical foaming-crosslinking simultaneous molding" process lies in the following: By feeding materials with different foaming agent contents into three sections, under the mixing action of the screw in extruder B, the three melts form radial stratification (rather than complete mixing) within the die head. After exiting the die head, due to the sudden pressure drop, the foaming agent decomposes and generates gas. Under the constraint of the crosslinking network, a gradient cell structure with decreasing density along the radial direction is formed. The inner layer has a low foaming agent content (131), small cells, and high density, ensuring insulation strength; the outer layer has a high foaming agent content (133), large cells, and low density, providing buoyancy.

[0046] Step S2: Longitudinal water-blocking layer 15 wrapping Outside the insulation shielding layer, two water-blocking tape wrapping machines are used to wrap the expansion-type water-blocking tape in opposite directions (one layer clockwise and one layer counterclockwise) with an overlap rate of 30~35%. The wrapping tension is controlled at 15~25N to ensure that the water-blocking tape is tightly attached to the insulated wire core.

[0047] Step S3: Metal shielding layer 16 encapsulation Use a copper strip longitudinal wrapping machine or braiding machine to wrap copper strip (longitudinal wrapping overlap rate ≥15%) or braid tin-plated copper wire (braiding density 80~85%) around the longitudinal water-blocking layer 15. If it is copper strip longitudinal wrapping, argon arc welding or ultrasonic welding should be used at the copper strip overlap to ensure electrical continuity.

[0048] Step S4: Extrusion of closed-cell foamed buoyancy buffer layer 2 The three-core stranded cable was produced using a single-screw extruder (L / D=25:1) with extrusion temperatures set as follows: Zone 1 160℃, Zone 2 180℃, Zone 3 200℃, and die head 190℃. The material formulation was: PP (MFR=3.0g / 10min, homopolymer): 100 phr; foaming agent AC: 6 phr; foaming aid (zinc oxide and zinc stearate compound, 1:1): 2 phr; antioxidant 1010: 0.5 phr; nucleating agent (talc, particle size 5μm): 1 phr.

[0049] After extrusion, the material is cooled in a water tank (20~30℃). Since PP is a non-crosslinked system, no vulcanization pipe is needed; foaming is completed in the air between the extruder head and the cooling water tank. The expansion ratio of the foamed layer is controlled by adjusting the traction speed (10~20m / min) to achieve a density of 0.55~0.65g / cm³. 3 The foam pore size is 50~100μm and the closed-cell rate is ≥75%.

[0050] Step S5: Steel Wire Armor Layer 3 A cage-type armoring machine is used, employing a two-layer, intermittently spaced armoring process with galvanized steel wire. The first layer of wire is left-handed, and the second layer is right-handed, with each layer containing the same number of wires and having the same pitch (pitch diameter ratio 12~16). The pitch directions of the two layers are opposite to counteract torsional loads. Water-blocking rope (polypropylene fiber absorbent rope with a water absorption rate ≥50 times) is filled between the armoring layers. After armoring, molten asphalt (temperature 180~200℃) is sprayed onto the surface of the steel wire to form an anti-corrosion layer.

[0051] Step S6: Extrusion of the weather-resistant sheath layer 4 A single-screw extruder (L / D=20:1) was used, with extrusion temperatures of 140℃ in zone 1, 160℃ in zone 2, 175℃ in zone 3, and 170℃ at the die head. The sheath material formulation was as follows: weather-resistant thermoplastic polyurethane (polyester type, hardness 85A): 60 phr; chlorinated polyethylene (chlorine content 35%): 30 phr; ethylene-vinyl acetate copolymer (VA content 18%): 10 phr; UV stabilizer UV-531: 2 phr; antioxidant 1010: 2.0 phr; and mildew inhibitor (Kasson CG, isothiazolinone): 1.0 phr.

[0052] After extrusion, the material is cooled in a water tank (water temperature 15~25℃), with a traction speed of 15~25m / min. The sheath surface is monitored by an online laser diameter gauge to ensure uniform thickness (deviation ≤0.2mm).

[0053] After the finished cable undergoes a spark test (10kV power frequency spark tester to check the integrity of the sheath) and visual inspection, it is wound into a steel cable reel with a reel diameter ≥20D (D is the outer diameter of the cable) to prevent damage to the foamed insulation layer due to excessively small bending radius.

[0054] Testing procedures and data: Test 1: Electrical Performance Testing Test objective: To verify the insulation reliability of the closed-cell foamed buoyancy buffer layer at a voltage level of 10kV.

[0055] Test standards: GB / T 3048, GB / T 12706.2, IEC 60502-2.

[0056] Sample preparation: Cut insulated cores from the finished cable (remove shielding layer and external structure), prepare 1mm thick insulation test pieces (samples from the inner layer, middle layer and outer layer respectively), and whole cable samples (10m in length).

[0057] Experimental procedures and data: (1) Power frequency withstand voltage test. Test method: According to GB / T 3048.8, a power frequency AC voltage was applied between each conductor and the metal shielding layer of the entire cable sample (10m in length). The test voltage was 4U0 (i.e., 4×8.7kV=34.8kV) and the duration was 4h. Test results: The sample did not break down, the leakage current was stable, and the test was passed.

[0058] (2) Partial discharge test. Test method: According to GB / T 3048.12, apply an AC voltage of 1.73U0 (i.e., 1.73×8.7kV≈15.0kV) to the sample and measure the partial discharge quantity. The detection sensitivity is ≤5pC. Test result: The partial discharge quantity is 1.2pC, which is far below the standard requirement (≤5pC). The test is passed.

[0059] (3) Insulation resistance test. Test method: According to GB / T 3048.5, the insulation resistance between the conductor and the metal shielding layer is measured at 20℃. Test result: The insulation resistance is 8.5 × 10⁻⁶. 4 The MΩ·km value is far higher than the standard requirement (≥1000 MΩ·km), and the test was passed.

[0060] (4) Dielectric loss tangent (tanδ) test. Test method: According to GB / T 3048.11, apply the rated voltage U0 (8.7kV) between the conductor and the metal shielding layer, and measure the dielectric loss tangent. Test result: tanδ=0.0008 (20℃), which is far below the standard requirement (≤0.001), and the test is passed.

[0061] (5) Impulse voltage test, test method: apply 10 positive and 10 negative lightning impulse voltages to the sample in accordance with GB / T 3048.13, with an impulse voltage peak of 75kV (corresponding to Class B impulse level of 10kV cable).

[0062] Test results: The sample did not break down, and the test was passed.

[0063] (6) Insulation breakdown field strength test, test method: in accordance with GB / T 1408.1, the 1mm thick insulation test piece in the three regions shall be subjected to power frequency breakdown test, ball-ball electrode, voltage rise rate 500V / s.

[0064] Experimental results: Inner layer (high-density layer): breakdown field strength is 38.5 kV / mm; Middle layer (transition layer): Breakdown field strength is 33.2 kV / mm; Outer layer (low-density layer): breakdown field strength is 30.8kV / mm; the overall insulation layer has an equivalent breakdown field strength ≥30kV / mm, meeting the 10kV voltage level requirements.

[0065] (7) Space charge distribution test. Test method: The pulse electroacoustic method (PEA method) was used. A DC electric field of 30 kV / mm was applied to the sample and held for 30 min before measuring the space charge density distribution. Test results: Space charge density ≤ 1.8 C / m 3 It meets the design requirements (≤2C / m) 3 ).

[0066] Experiment 2: Mechanical Performance Testing Test objective: To verify the mechanical strength and flexibility of the gradient foamed insulation layer and the overall cable.

[0067] Test standards: GB / T 2951, GB / T 12706.2.

[0068] Experimental procedures and data: (1) Tensile properties test of insulation layer. Test method: Prepare dumbbell-shaped specimens from three regions according to GB / T 2951.11 and test them at 23℃ and tensile rate of 250mm / min.

[0069] The experimental results are shown in the table below:

[0070] (2) Thermal elongation test of insulation layer. Test method: According to GB / T 2951.21, the sample is kept at 200℃ and 0.2MPa load for 15min, and the elongation and permanent elongation under load are measured.

[0071] Test results: Elongation under load was 65%, and permanent elongation after cooling was 8%, which meets the standard requirements (elongation under load ≤175%, permanent elongation ≤15%).

[0072] (3) Cable bending test. Test method: According to GB / T 12706.2, the cable is wound around a cylinder with a diameter of 20D (D=67mm, i.e., bending diameter 1340mm) and bent three times in each direction. Test results: There are no cracks on the cable surface, no damage to the insulation layer, and the partial discharge is still ≤5pC. The test is passed.

[0073] (4) Determination of minimum bending radius of cable. Test method: Gradually reduce the bending radius until visible cracks appear in the insulation layer or sheath. Test results: The minimum bending radius is 12D (804mm), which is better than that of traditional solid XLPE cables (usually ≥15D). This is due to the flexible outer layer structure of the gradient foamed insulation layer.

[0074] Experiment 3: Buoyancy Performance Testing Test objective: To verify the overall density of the cable and its floating stability in water.

[0075] Test basis: Refer to ASTM D792 (density determination) and GB / T 1033 (plastic density and relative density test methods).

[0076] Experimental procedures and data: (1) Determination of overall cable density: The test method was as follows: the mass per unit length of the cable and the volume of water drained were measured in pure water at 20℃, and the overall density was calculated. Test results: The overall density of the cable was 0.89 g / cm³. 3 It meets the design requirements (0.87~0.92g / cm³). 3 It has a density lower than that of water (1.0 g / cm³). 3 It can float on its own.

[0077] (2) Freshwater floating test. Test method: A 5m long cable sample was placed horizontally in a standard freshwater pool (water temperature 20℃, water depth ≥2m), and the floating state was observed. Test results: The cable floated steadily on the water surface, with a floating height of about 8%~12% (i.e., 8%~12% of the cable diameter was exposed above the water surface). The floating posture was stable and there was no overturning phenomenon. After standing for 72 hours, the floating state remained unchanged.

[0078] (3) Seawater floating test, test method: place the cable sample in artificially prepared standard seawater (salinity 35‰, density 1.025g / cm³). 3 The cable was observed to float in seawater at a temperature of 20℃. Results: The cable floated approximately 5% to 8% above the surface in seawater and remained stable. After 72 hours of settling, no salt crystals adhered to the sheath surface, and the floating state remained unchanged.

[0079] (4) Buoyancy decay test (long-term immersion). Test method: Immerse the cable sample in fresh water for 30 days, 60 days and 90 days, and measure the overall density change and buoyancy retention rate of the cable periodically.

[0080] The experimental results are shown in the table below:

[0081] The buoyancy reduction mainly stems from the slow infiltration of trace amounts of water through the sheath layer, but it still meets the self-floating requirement after 90 days.

[0082] (5) Buoyancy buffer layer density determination: The closed-cell foamed buoyancy buffer layer was peeled off from the cable, and the density was determined using the density gradient column method. Test results: The density of the buoyancy buffer layer was 0.58 g / cm³. 3 The closed-cell rate is 82%, meeting the design requirements (density 0.55~0.65g / cm³). 3 (Closed-cell ratio ≥75%).

[0083] Test 4: Weather Resistance Test Test objective: To verify the long-term weather resistance of the cable in a marine environment.

[0084] Tests were conducted in accordance with GB / T 2951 (aging test), GB / T 2423 (environmental test), and ASTM G154 (ultraviolet aging).

[0085] Experimental procedures and data: (1) UV aging resistance test. Test method: According to ASTM G154, the weather-resistant sheath sample was irradiated with a UV-A340 lamp with an irradiance of 0.89 W / (m²·nm). The irradiation cycle was 8h UV + 4h condensation, with a cumulative irradiation of 1000h. Test results: The sheath surface showed no powdering or cracking, the tensile strength retention rate was 92%, the elongation at break retention rate was 88%, and the color difference ΔE ≤ 3.0, meeting the requirements for long-term outdoor use.

[0086] (2) Salt spray corrosion resistance test. Test method: According to GB / T 2423.17, a neutral salt spray test (NaCl concentration 5%, temperature 35℃, continuous spraying) was conducted on the entire cable sample. Test results: 500h: The steel wire armor layer showed no rust, and the sheath surface showed no change; 1000h: Slight white rust appeared on the surface of the galvanized steel wire (area <5%), and there was no change on the surface of the sheath; 2000h: The area of ​​white rust on the surface of the galvanized steel wire is less than 15%, with no red rust, and the sheath surface remains intact. The asphalt anti-corrosion layer and the weather-resistant sheath layer work together to provide excellent salt spray resistance.

[0087] (3) Microbial resistance (anti-mold) test. Test method: According to GB / T 2423.16, the sheath sample was exposed to a mixed mold spore suspension (Aspergillus niger, Aspergillus flavus, Chaetomium globosum, etc.) and cultured for 28 days at a temperature of 28~30℃ and a relative humidity of ≥95%. Test results: The mold growth level on the sheath surface was 0 (no growth), indicating excellent anti-mold performance and meeting the requirements for use in humid environments such as aquaculture.

[0088] (4) Seawater immersion aging test. Test method: Immerse the cable sample in artificial seawater at 60°C for 7 days, 14 days and 28 days respectively to accelerate aging and test the insulation resistance and sheath mechanical properties.

[0089] The experimental results are shown in the table below:

[0090] Both insulation resistance and mechanical performance degradation are within acceptable ranges.

[0091] Experiment 5: Dynamic Bending Fatigue Testing Test objective: To verify the fatigue resistance of the cable under dynamic loads such as swaying of a floating platform and impact of wind and waves.

[0092] Test basis: Refer to the dynamic bending test method in IEC 61400-4 and the dynamic bending test specification for submarine cables.

[0093] Experimental procedures and data: (1) Dynamic bending test, test method: a cable sample with a length of 10m is installed on a dynamic bending tester, the bending radius is set to 15D (1005mm), and the cable is bent at a frequency of 0.5Hz at ±90°.

[0094] The experimental results are shown in the table below:

[0095] The electrical performance still meets the standard requirements after 100,000 dynamic bending cycles, proving that the cable has excellent fatigue resistance.

[0096] (2) Torsional fatigue test, test method: fix the cable sample to the torsion test device and apply ±180° torsion (for a cable length of 10m, the torsion angle is about ±1° / m), frequency 0.3Hz.

[0097] Experimental results: After 5000 torsion cycles: there is no loosening of any layer of the cable structure, and no breakage of the steel wire armor layer; After 10,000 torsion cycles: the cable structure remains intact, and the electrical performance test is passed. The double-layer reverse armor structure effectively counteracts the torsional load.

[0098] Test 6: Water-blocking performance test Test objective: To verify the water-blocking ability of the cable under immersion conditions.

[0099] Test standards: GB / T 12706.2, IEC 60502-2.

[0100] Experimental procedures and data: (1) Longitudinal water blocking test. Test method: According to the requirements of Appendix GB / T 12706.2, the sheath and armor layer are stripped from one end of the cable to expose the water blocking layer. The cable is vertically immersed in water (water temperature 20℃), with the water level 500mm above the stripped end, and kept for 72h. Test results: The water penetration distance along the longitudinal direction of the cable is 0mm (i.e., no penetration). The water blocking strip fully expands and blocks water migration, and the longitudinal water blocking performance is excellent.

[0101] (2) Radial water resistance test (water pressure penetration test), test method: Seal both ends of a 3m long cable sample, place it in a water pressure test device, apply a water pressure of 0.5MPa, and maintain for 72h. Test results: There was no water seepage inside the cable, the insulation resistance did not decrease significantly, and the radial water resistance performance met the requirements.

[0102] Experiment 7: Thermal Cycling and Current Carrying Capacity Detection Test objective: To verify the performance stability of the cable under long-term operating temperature rise conditions.

[0103] Test standards: GB / T 12706.2, IEC 60502-2.

[0104] Experimental procedures and data: (1) Thermal cycling voltage test, test method: Apply 2U0 (17.4kV) AC voltage to the cable in accordance with GB / T 12706.2, and perform 20 thermal cycles (heat the conductor to 90~95℃ and cool it to the ambient temperature, each cycle is about 8 hours).

[0105] Test results: During 20 thermal cycles, the cable did not break down, and the partial discharge was always ≤5pC. The test was passed.

[0106] (2) Current carrying capacity temperature rise test. Test method: Under ambient temperature of 25℃ and natural convection conditions, the rated current carrying capacity current is passed through the cable conductor, and the conductor temperature is measured after thermal equilibrium is reached.

[0107] The experimental results are shown in the table below:

[0108] Although the microporous structure of the gradient foamed insulation layer reduces the thermal conductivity, the addition of two-dimensional boron nitride nanosheets effectively compensates for the heat dissipation capacity, and the current carrying capacity is comparable to that of solid XLPE cables.

[0109] Experiment 8: Microstructure Characterization of Foamed Insulation Layer Experimental objective: To verify whether the microstructure of the gradient foamed insulation layer meets the design requirements.

[0110] Test basis: Refer to ASTM D3576 (Determination of cell size in foam plastics).

[0111] Experimental procedures and data: (1) Observation of cell morphology (SEM): Samples were taken from three regions, and gold was sprayed after liquid nitrogen fracture. The cell morphology was observed using a scanning electron microscope (SEM).

[0112] The experimental results are shown in the table below:

[0113] The three-layer bubble structure is clear, the interface transition is smooth, and there are no delamination or large pore defects.

[0114] (2) Determination of closed-pore rate. Test method: The closed-pore rate of the three regions was determined by the gas gravity method.

[0115] The experimental results are shown in the table below:

[0116] All meet the design requirements.

[0117] (3) Density gradient verification, test method: The density distribution was measured point by point along the radial direction of the insulating layer using a micro densitometer. Test results: The density decreased continuously from the inside to the outside, with the inner layer having a density of 0.89 g / cm³. 3 →Middle layer 0.81g / cm 3 →Outer layer 0.69g / cm 3 Consistent with the formulation design, there are no mutations in the transition region.

[0118] Test 9: Performance Testing of the Sheath Layer Test objective: To verify the comprehensive performance of the weather-resistant sheath layer.

[0119] Test standards: GB / T 2951, GB / T 12706.2.

[0120] Experimental procedures and data: (1) Mechanical properties of the sheath, test method: Prepare dumbbell-shaped specimens of the sheath according to GB / T 2951.11, and test the tensile strength and elongation at break. Test results: tensile strength 22.5MPa, elongation at break 450%, which meets the standard requirements (tensile strength ≥15MPa, elongation at break ≥300%).

[0121] (2) Sheath heat aging test. Test method: According to GB / T 2951.12, the sheath sample was aged in an oven at 100℃ for 168h, and the mechanical properties after aging were tested. Test results: Tensile strength retention rate was 94%, and elongation at break retention rate was 91%, which met the standard requirements (retention rate ≥80%).

[0122] (3) Sheath abrasion resistance test. Test method: According to GB / T 2951.28, the Taber abrasion tester (CS-17 grinding wheel, 1000g load, 1000 rpm) was used. Test results: The mass loss was 45mg, which is better than that of ordinary CPE sheaths (usually 60~80mg). The TPU component significantly improved the abrasion resistance.

[0123] (4) Oil resistance test of the sheath. Test method: Immerse the sheath sample in IRM902 standard oil at 100℃ for 24 hours, and test the mass change and mechanical properties. Test results: Mass change rate +2.1%, tensile strength retention rate 91%, elongation at break retention rate 88%, which meets the standard requirements.

[0124] Experiment 10: Comprehensive Comparative Experiment Experimental objective: To compare the performance of the cable of this invention with that of traditional solid XLPE insulated cables and external float-type floating cables.

[0125] (1) Comparison of density and buoyancy, the test results are shown in the table below:

[0126] The cable of this invention maintains its self-floating ability while having the smallest outer diameter, lightest weight, and best bending performance.

[0127] (2) Comparison of insulation performance, the test results are shown in the table below:

[0128] The insulation breakdown field strength (especially in the inner high-density area) of the cable of this invention is higher than that of traditional XLPE cables, which is due to the synergistic effect of nano-alumina and voltage stabilizer; the partial discharge quantity and space charge density are also better than those of traditional cables.

[0129] (3) Economic comparison Taking a 1000m cable laying project as an example: The experimental results are shown in the table below:

[0130] The cable of this invention reduces the overall cost by approximately 33% to 43% because it does not require an external buoyancy device, and it is also simple to maintain and highly reliable.

[0131] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art can make various modifications or equivalent substitutions to the present invention within the scope of its essence and protection. Such modifications or equivalent substitutions should also be considered to fall within the protection scope of the present invention.

Claims

1. A floating 10kV power cable, characterized in that, From the inside out, the cable comprises a three-core stranded conductor, a closed-cell foamed buoyancy buffer layer, a steel wire armor layer, and a weather-resistant sheath layer. Each stranded conductor, from the inside out, comprises a conductor, a conductor shielding layer, a gradient foamed insulation layer, an insulation shielding layer, a longitudinal water-blocking layer, and a metal shielding layer. The density of the gradient foamed insulation layer is distributed radially in a gradient manner, with the inner layer having a higher density than the outer layer. The gradient foamed insulation layer comprises a matrix resin, additives, a foaming system, and a crosslinking system. The matrix resin is a blend of low-density polyethylene and ethylene-vinyl acetate copolymer. The additives include one-dimensional potassium titanate whiskers, two-dimensional boron nitride nanosheets, and nano-alumina with surface-grafted voltage stabilizers. The overall density of the cable is 0.87~0.92 g / cm³. 3 .

2. A floating 10kV power cable according to claim 1, characterized in that: The thickness of the gradient foamed insulation layer is 4.5~5.5mm, and the gradient foamed insulation layer includes an inner layer, a middle layer and an outer layer; The inner layer accounts for 30% of the overall thickness and has a density of 0.88~0.92 g / cm³. 3 Pore ​​size 3~10μm, closed-porosity ≥92%; The intermediate layer accounts for 40% of the total thickness and has a density of 0.78~0.85 g / cm³. 3 Pore ​​size 10~25μm, closed-porosity ≥87%; The outer layer accounts for 30% of the overall thickness and has a density of 0.62~0.72 g / cm³. 3 Pore ​​size 25~45μm, closed-porosity ≥82%.

3. A floating 10kV power cable according to claim 2, characterized in that: In the matrix resin, the one-dimensional potassium titanate whiskers are K2O·6TiO2, and the amount added is 0.5~1.0 phr. The amount added of the two-dimensional boron nitride nanosheets is 1.0~2.0 phr. The amount added of the nano-alumina, which is grafted with the surface voltage stabilizer, is 2.0~3.0 phr, and the amount added decreases from the inner layer to the outer layer.

4. A floating 10kV power cable according to claim 1, characterized in that: The specific preparation method of the nano-alumina with surface-grafted voltage stabilizer is as follows: first, the nano-alumina is pretreated with silane coupling agent KH-570 to obtain modified nano-alumina with double bonds on the surface, and then the voltage stabilizer N-(4-anilinephenyl)-maleimide is grafted onto the surface of the nano-alumina by free radical polymerization, with a grafting rate of 12~18wt%.

5. A floating 10kV power cable according to claim 1, characterized in that: The crosslinking system comprises: 1.5-2.5 phr of dicumyl peroxide, 0.5-1.0 phr of triallyl isocyanurate as a co-crosslinking agent, and 0.5 phr of antioxidant 1010; The foaming system comprises: 2.5-4.5 phr of azodicarbonamide coated with stearic acid as the main foaming agent, 1.0-2.0 phr of sodium bicarbonate as the auxiliary foaming agent, and 0.3-0.5 phr of zinc oxide and 0.3-0.5 phr of zinc stearate as foaming activators.

6. A floating 10kV power cable according to claim 1, characterized in that: The three-core stranded conductor is made of copper stranded conductor with a cross-section of 50~400mm², and the conductor shielding layer is made of semi-conductive cross-linked polyethylene with a thickness of 0.6~1.0mm.

7. A floating 10kV power cable according to claim 1, characterized in that: The insulating shielding layer is made of semi-conductive cross-linked polyethylene with a thickness of 0.6~1.0 mm; The longitudinal water-blocking layer is set by overlapping and wrapping double-layer water-blocking tape with an overlap rate of ≥30%. The water-blocking tape is an expansion type with a thickness of 0.5mm, an expansion rate of ≥10mm / min, an expansion height of ≥12mm, and contains more than 60wt% superabsorbent polymer (SAP). The metal shielding layer is made of longitudinally wrapped copper strip or tinned copper wire. The copper strip is ≥0.1mm thick and its width matches the outer diameter of the cable. The tinned copper wire has a braiding density ≥80% and a single wire diameter of 0.15~0.20mm. The closed-cell foamed buoyancy buffer layer is made of closed-cell foamed polypropylene, with a minimum thickness of 3.0~5.0 mm and a density of 0.55~0.65 g / cm³. 3 Foaming pore size 50~100μm, closed-cell rate ≥75%; The steel wire armor layer is made of galvanized steel wire with a double-layer gap armor, with a diameter of 1.5~3.0mm. The gaps in the armor are filled with water-blocking rope. The steel wire armor layer is coated with an asphalt anti-corrosion layer with a thickness of 0.5~1.0mm.

8. A floating 10kV power cable according to claim 1, characterized in that: The weather-resistant sheath layer is a blend of weather-resistant thermoplastic polyurethane, chlorinated polyethylene and ethylene-vinyl acetate copolymer in a mass ratio of 6:3:1, with added UV-resistant additive UV-531 at 2.0 phr, mildew inhibitor isothiazolinone at 1.0 phr and antioxidant 1010 at 2.0 phr. The thickness of the weather-resistant sheath layer is 3~3.5 mm.

9. A method for manufacturing a floating 10kV power cable according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1 employs a three-segment feeding, three-layer co-extrusion and gradient chemical foaming cross-linking synchronous molding process to sequentially form a conductor shielding layer, a gradient foaming insulation layer and an insulation shielding layer on the outside of the conductor. S2, a longitudinal water-blocking layer is wrapped around the outside of the insulating shielding layer; S3, covered with a metal shielding layer; S4, three-core stranded cable, gap extruded closed-cell foamed buoyancy buffer layer; S5, galvanized steel wire forms a steel wire armor layer through a double-layer gap-type armor; S6, extruded weather-resistant sheath layer.

10. A method for manufacturing a floating 10kV power cable according to claim 9, characterized in that: Step S2 specifically involves: An extrusion unit consisting of three tandem single-screw extruders and a three-layer co-extrusion crosshead is used to continuously complete the molding of the conductor shielding layer, the gradient foamed insulation layer and the insulation shielding layer, respectively. The barrel of the intermediate single-screw extruder is divided into three temperature-controlled sections. Different uniformly mixed gradient foamed insulation layer materials with different formulations are fed into each section through an independent loss-in-weight feeder. The gradient foamed insulation layer materials extruded from the die head form radial layers and directly enter the horizontal vulcanizing tube for foaming and cross-linking. The horizontal vulcanizing tube is filled with high-purity nitrogen and is divided into three sections. The first section accounts for 20% of the length and has a temperature of 185~190℃, the second section accounts for 50% of the length and has a temperature of 205~220℃, and the third section accounts for 30% of the length and has a temperature of 165~170℃. After cooling and shaping in a cooling water tank, the gradient foamed insulation layer is formed.

Citation Information

Patent Citations

  • Floating power cable based on communication engineering

    CN120280207A

  • Water-floating cable

    CN108597660A

  • Floating type water photovoltaic dynamic cable and manufacturing method thereof

    CN121011402A